Experience of establishing an acute geriatric outreach service versus subacute service to nursing homes. Issue 11 (1st November 2018) - Chan, Daniel K. Y.; Liu, Frank X.; Irwanto, Deni; Prasetyo, Davin; Ozorio, Gerard; Li, Feika; Smith, Matthew; Sharma, Anurag; Chen, Jack
Abstract: To share our experience of establishing an acute outreach service to nursing homes and to evaluate the impact of such service on emergency department presentations, data were drawn from a pre‐existing database from 2013 to 2017. Of the 986 acute patients treated in 12 nursing homes over a 23‐month period, the acute geriatric outreach service was shown to be safe, with few adverse events (one allergic reaction) and 5.3% of patients required transfer to hospital. The acute service decreased emergency department presentation of nursing home patients by 10% compared to the subacute service (incidence rate ratio = 0.90; 95% confidence interval: 0.84–0.96; P = 0.001). Cost–benefit analysis showed for every $1 spent, a saving of $5 was realised.